Characterization of extracellular vesicles by flow cytometry: Challenges and promises. (October 2022) - Gul, Banat; Syed, Feryal; Khan, Shamim; Iqbal, Abid; Ahmad, Iftikhar
Abstract: The International Society for Extracellular Vesicles (ISEV) defines the extracellular vesicle (EV) as "the particles naturally released from the cell that are delimited by a lipid bilayer and cannot replicate, i.e. do not contain a functional nucleus". The size (diameter) of EVs ranges in ~30–1000 nm, with peak population at ~ 100 nm. Flow cytometry (FCM) is the most commonly used technique for analysis of EVs. However, accurate characterization, procedure standardization, instrument calibration and results interpretation/validation of EVs is confounded by their complex and variable composition, small size and substantial differences in physiological concentrations. Here, the challenges to and promises of FCM for characterization of EVs are discussed. Specifically, we systematically reviewed the pitfalls of FCM in the detection of (small) EVs and the corresponding strategies for enhancing the sensitivity and resolution of the instrument. The shortcomings and improvement in the overall FCM system are described in terms of reference material for calibration, the collection optics for fluorescence (FL), side scatter (SSC) and forward scatter (FSC) signals and fluidics. This study may provide a comprehensive reference for a brief overview pertaining to the challenges and promises of a modern FCM system for analysis of EVs. Graphical Abstract: ga1 Highlights: Extracellular vesicle (EV) is a cell-secreted, heterogeneous group of nanoscopic particles. The most commonly used method for EV analysis is flow cytometry (FCM). FCM is capable for size characterization, enumeration and phenotyping of EVs. Heterogeneity in biogenesis, size, biochemical composition and concentration hinder appropriate analyses of EVs. Factors degrading the sensitivity of FCM and promises to these pitfalls are outlined.